ILLOCUTIONARY ACT ON DONALD TRUMP’S SPEECH “CORONAVIRUS TASK FORCE BRIEFING” IN 2020 - Septiana Sari Laia (Universitas Nias Raya, 2023)
This research aimed at identifying the type of illocutionary act and the function of illocutionary act in President Donald Trump’s speech about Coronavirus Task Force Briefing in 2020. This research was designed by using Qualitative research method. The data was analyzed by using the theory of Miles, et all (2014:31-33). The result of this research showed that there were five types illocutionary act namely: verdictives, exercitives, commisives, behabitives, and expositives. Those illocutionary act found function to as evaluate, suggest, advice, promise, appreciate, and explain. Based on the results, it can be concluded expositives become as the dominant types of illocutionary act used in Donald Trump’s speech. It is suggested that illocutionary should be learned and more understand deeply.